AD.0015

   Решите уравнение:

      4^(1/x) + 6^(1/x) — 9^(1/x) = 0.

   1. Разделим обе части уравнения на 9^(1/x):

      4^(1/x) + 6^(1/x) — 9^(1/x) = 0;

      (4/9)^(1/x) + (6/9)^(1/x) — 1 = 0;

      ((2/3)^(1/x))^2 + (2/3)^(1/x) — 1 = 0.

   2. Обозначим:

      y = (2/3)^(1/x) и решим уравнение:

      y^2 + y — 1 = 0;

      D = 1 + 4 = 5;

      y = (-1 ± √5)/2.

   3a. y = (-1 — √5)/2;

      (2/3)^(1/x) = (-1 — √5)/2 < 0, не имеет решения.

   3b. y = (-1 + √5)/2 ;

      (2/3)^(1/x) = (-1 + √5)/2 ;

      (1/x) * ln(2/3) = ln (-1 + √5) — ln2 ;

      1/x = ( ln (√5 — 1) — ln2 ) / ln(2/3);

      x = (ln2 — ln3) / ( ln (√5 — 1) — ln2 ).

   Ответ: (ln2 — ln3) / ( ln (√5 — 1) — ln2 ).

Добавить комментарий

Ваш адрес email не будет опубликован.